THE RELATIONSHIP OF MARINE TOURISM DEVELOPMENT TO THE WELFARE OF LOCAL COMMUNITIES POST PANDEMIC COVID-19 AT NORTH RUPAT LAPIN BEACH - Haziki, Kezya Putri; Darwis; Warningsih, Trisla (Riau International Conference on Economics, Business and Accounting, 2024)
This research was carried out in July 2023 at Lapin Beach, Rupat Island, North Rupat District, Bengkalis Regency, Riau Province. The aim of this research is to analyze the development of marine tourism, the welfare of local communities and analyze the relationship between the development of marine tourism at Lapin Beach and the welfare of local communities after the Covid-19 pandemic. Sampling was carried out using the Non-probability Sampling method , namely 30 business owners and 11 local workers. Data collection techniques used in this research include interviews, in-depth interviews, observation and documentation. The data analysis used in this research is a quantitative approach supported by qualitative data with a means of measuring the level of welfare according to BPS which was proposed in 2015. The results of this research show that the development of marine tourism on Lapin Beach after Covid-19 shows an increase in the number of percentages, namely in the type attractiveness of natural resources, type of infrastructure, level of accessibility, and level of community participation compared to during the Covid-19 pandemic. The welfare of local communities does not show significant changes, namely in the level of income, level of expenditure, level of living conditions, level of ease of accessing education, level of ease of accessing health services. The relationship between marine ecotourism development and the welfare of local communities. The results of the analysis show that there is a significant relationship between the development of marine tourism and the welfare of local communities. Keywords : Tourism Development, Community Welfare